Revenue Administration : Functionally Organized Tax Administration - Kidd, Maureen (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note analyzes the functionally organized tax administration. The organization structure of tax organizations has evolved considerably over time. From organization structures based on type of tax, to those based on function, to those based on the type of taxpayer, economies of different sizes and at different stages of development have attempted different kinds of organizational reform. This note explains why the choice of an organizational model is so important. The paper also describes key components of a function-based organization.